Addiction in Anesthesiology : Sometimes Sh*t Happens - Widnyana, I Made Gede; Senapathi, Tjokorda Gde Agung; Lolobali, Marilaeta Cindryani (Bali Journal of Anesthesiology, 2018)
Anesthesiology demands a vigilant and controlled cautious person with a good tempered manner and professional character. Those virtues and values were built through thousands of trials, errors, failures, chances and breakdowns. When some individuals could resist and thrive, others may fall and surrender. Anesthesiologists are responsible of patients beneficiary with the utmost point should be considered in patient physical safety and survival. The aim to become a good anesthesiologist who keeps the safety and patient wellbeing sometimes had taken its toll by sacrificing the wellbeing of the anesthesiologists themselves.